Porous Concrete As Road Infrastructure Using Coarse Aggregate Uniform Gradation - Andi Muhammad Rezky Putra Ardian; Adnan Adnan; Abd. Muis Baharuddin (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
Porous concrete is commonly used in road linings with minimal traffic, parking areas, pedestrian paths, and parks. The strength of porous concrete depends on the size of the aggregate and the correct composition of water and cement. The objective of the study was to analyse the effect of cement water factor in uniformly graded porous concrete on compressive strength and permeability in uniformly graded porous concrete on permeability values. The relationship between the compressive strength of concrete tends to decrease as the value of cement water factor increases. The water-cement factor strongly influences the permeability value. The greater the value of cement water factor, the smaller the permeability of uniformly graded porous concrete, this is due to the deposition of cement water at the base of the slab. The use of super plasticizer (SP) in porous concrete accelerates the pavement process, but does not improve permeability. cement water factor 0.35 with a 28-day treatment period obtained a Slump test value of 178 mm, cement water factor 0.5 of 192 mm, cement water factor 0.6 with a 28-day treatment period obtained a Slump test value of 196 mm. while porous concrete with a cement water factor of 0.35 has an average compressive strength of 6.13 Mpa, while a cement water factor of 0.50 has an average compressive strength of 5.47 Mpa, and a cement water factor of 0.60 has an average compressive strength of 5.00 Mpa.